2017
DOI: 10.18632/oncotarget.15369
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic BCR-ABL fusion gene as variant rearrangement in chronic myeloid leukemia: molecular cytogenetic characterization and influence on TKIs therapy

Abstract: At diagnosis, about 5% of Chronic Myeloid Leukemia (CML) patients lacks Philadelphia chromosome (Ph), despite the presence of the BCR/ABL rearrangement. Two mechanisms have been proposed about the occurrence of this rearrangement: the first one is a cryptic insertion between chromosomes 9 and 22; the second one involves two sequential translocations: a classic t(9;22) followed by a reverse translocation, which reconstitutes the normal morphology of the partner chromosomes. Out of 398 newly diagnosed CML patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 22 publications
0
10
0
1
Order By: Relevance
“…One of the major challenges for technologists who perform the final analysis of a BCR-ABL1 FISH test is to recognize all possible unusual signal patterns and distinguish them from background noise (especially when the FISH test is performed on BM/PB smear specimen and a low positive rate exists). An unusual signal pattern is defined here as a signal pattern other than the dominant patterns of 2R1G1F for p210 and 1R1G2F for p190, representing likely existence of cells with variant breakpoints and/or BCR-ABL1 fusion through a different mechanism, e.g., insertion [9,11]. Cases with one or more copies of additional Ph+ are relatively commonly observed in our practice, and our technologists are familiar with this phenomenon.…”
Section: Unusual Signal Patternsmentioning
confidence: 99%
“…One of the major challenges for technologists who perform the final analysis of a BCR-ABL1 FISH test is to recognize all possible unusual signal patterns and distinguish them from background noise (especially when the FISH test is performed on BM/PB smear specimen and a low positive rate exists). An unusual signal pattern is defined here as a signal pattern other than the dominant patterns of 2R1G1F for p210 and 1R1G2F for p190, representing likely existence of cells with variant breakpoints and/or BCR-ABL1 fusion through a different mechanism, e.g., insertion [9,11]. Cases with one or more copies of additional Ph+ are relatively commonly observed in our practice, and our technologists are familiar with this phenomenon.…”
Section: Unusual Signal Patternsmentioning
confidence: 99%
“…Luatti et al reported six cases of CML who presented with an NK during cytogenetic analysis at the time of diagnosis, and all the cases received imatinib therapy. Among them, four patients with low-risk Sokal scores achieved complete cytogenetic response at a median time of 24.5 months after receiving imatinib; one patient with a high-risk Sokal score developed imatinib resistance and demonstrated a major molecular response after switching to nilotinib; and only one patient with a moderate-risk Sokal score received allo-HSCT without remission and relapse (11). They concluded that the clinical benefit of TKIs in patients with NK/BCR-ABL1 + is similar to that in patients with Ph + , and this view is also recognized by Bennour et al (13).…”
Section: ' Discussionmentioning
confidence: 99%
“…At the time of disease diagnosis, cytogenetic analysis showed that the cryptic Ph chromosome translocation could present with a normal karyotype (NK) in approximately 3.0%-7.7% of CML patients, as well as a relatively small proportion of BCR-ABL1 + ALL patients (5)(6)(7)(8)(9)(10). The prognosis of NK in CML patients has been reported, and the results in the tyrosine kinase inhibitor (TKI) era were controversial (4,(11)(12)(13). However, its role has not been systematically elucidated in adult patients with BCR-ABL1-positive ALL.…”
Section: ' Introductionmentioning
confidence: 99%
“…Rövidítések AF = akcelerált fázis; allo-HSCT = (allogeneic hematopoietic stem cells transplantation) allogén haematopoeticus őssejtek átültetése; BT = blasztos transzformáció; CCA = (clonal cytogenetic abnormality) klonális citogenetikai eltérés; CF = (chron ic phase) krónikus fázis; CHR = (complete hematologic response) komplett hematológiai válasz; CML = (chronic myeloid leukemia) krónikus myeloid leukaemia; DLI = donorlymphocyta-infúzió; EBMT = (European Society for Bone Marrow Transplantation) Európai Csontvelő-transzplantációs Társaság; ELN = (European Leukemia Net) Európai Leukaemia Hálózat; GVHD = (graft-versus-host disease) graft versus host betegség; HLA = humán leukocytaantigén; IS = (international standard) nemzetközi standard; MMR = (major molecular remission) major molekuláris remisszió; MR = (molecular remission) molekuláris remisszió; PFS = (progression-free survival) progressziómentes túlélés; Ph = Philadelphia; RQ-PCR = (real-time quantitative polymerase chain reaction) valós idejű kvantitatív polimeráz-láncreakció; TKI = (tyrosine kinase inhibitor) tirozinkináz-gátló A krónikus myeloid leukaemia (CML) klonális myeloproliferativ megbetegedés, amely az őssejteket érinti [1,2]. A betegség molekuláris alapja a BCR-ABL fúziós génátrendeződés [3], amely a 9-es és a 22-es kromoszóma reciprok transzlokációja miatt jön létre [4]. A kromoszómatörés egy adott génen belül különböző helyeken történhet meg, ennek fügvényében megkülönböztetünk major, minor és mikro-BCR-ABL gént, amely az átíródott onkoprotein nagyságát tekintve 210 kD (p210 Bcr/Abl ), 190 kD (p190 Bcr/Abl ), illetve ritkábban 230 kD (p230 Bcr/Abl ).…”
Section: Eredeti Közleményunclassified